Photo-oxidation of EPDM/layered double hydroxides composites: influence of layered hydroxides and stabilizers - Kumar, B.; Rana, S.; Singh, R. P. (Express Polymer Letters, 2007)
The photo-oxidation of ethylene propylene diene monomer (EPDM)/layered double hydroxide (LDH) composites as well as EPDM/LDH with stabilizers is studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C for different time intervals. The development of functional groups during oxidation was monitored by FT-IR spectroscopy. The photo-degradation of the pristine polymer and composites take place and the increase in hydroxyl and carbonyl groups with irradiation times, was estimated. EPDM filled LDH showed higher degradation rate than pristine EPDM, while in acidic medium EPDM/LDH showed almost equal degradation as in isolated conditions. These results show the advantages of LDHs as a filler as well as an acid killer. The effect of stabilizers is very less because of their concentration in comparison of LDH.
Keywords: EPDM; layered double hydroxides; Photo-oxidation; polymer composites

Enhanced mineralization of gaseous organic pollutant by photo-oxidation using Au-Doped TiO2/MCM-41 - Tangale, Nilesh P.; Belhekar, Anuja A.; Kale, Kishor B.; Awate, Shobhana V. (Water Air and Soil Pollution, 2014)
The synthesis, characterization, and photocatalytic evaluation of titania-loaded MCM-41 with and without Au doping are reported in the present study. The samples were characterized by powder XRD, TEM, low temperature N-2 adsorption/desorption, UV-Vis, and FTIR. UV-induced vapor-phase photo-oxidation of acetone was used as a probe reaction to study the role of Au in mineralization of volatile organic compounds (VOCs), viz. acetone at different concentrations. The doping of Au in titania-loaded MCM-41 resulted in the decrease of BET surface area, total pore volume, and average pore size. UV-Vis diffuse reflectance spectra of Au-doped titania-loaded MCM-41 showed the red shift in their absorption bands compared to titania-loaded MCM-41. The activity of mineralization of acetone by photocatalysis for 2 % Au-doped titania-loaded MCM-41 was found to be similar to 1.6 times higher than titania-loaded MCM-41. The presence of cocatalytic nanosized gold might be responsible for their enhanced activity on account of the delayed recombination of electron/hole pair. Although, almost complete mineralization of acetone was observed irrespective of the initial concentration of acetone in air (up to 3.72 mol%) by all the catalysts, 2 wt.% Au-doped titania-loaded MCM-41 has shown the most enhanced activity.
Keywords: Acetone; Doping; Gold; Mineralization of VOCs; Photo-oxidation; TiO2/MCM-41